Anti-inflammatory and antioxidant activity of ethanolic extract of Bauhinia purpurea bark - Balaji Hari; T.K. Padmaja; P.Brahma Naidu; S. Roopa Naik; Balaji Meriga (International Journal of Drug Delivery, 2012)
The aim of this study was to evaluate the anti-inflammatory and antioxidant efficacy of ethanolic extract of Bauhinia purpurea bark (EBP) in Sprague Dawley (SD) rats. Carrageenan induced paw edema and air pouch inflammation, arachidonic acid induced ear edema and complete freundÊs adjuvant (CFA) induced hematological alterations were studied in control and experimental rats. Administration of EBP (200mg, 400mg, 600 mg/kg body weight) showed a significant and dose dependent inhibition of paw edema and ear edema and also reversed the hematological alterations near to normalcy. DPPH assay and measurement of MDA levels showed potent antioxidant activity of EBP. With increase in concentration of EBP, improvement in walking scores of motility test confirmed the anti-inflammatory activity of EBP. Acute toxicity studies demonstrated non toxic nature of EBP even at higher doses. Together, our results demonstrate that EBP has potent antiinflammatory as well as potent antioxidant properties validating the folk medicinal use of this species.